EDUKASI PENGELOLAAN KEUANGAN UMKM DALAM PEMISAHAN KEUANGAN PRIBADI DAN USAHA SEBAGAI UPAYA PENINGKATAN FINANCIAL AWARENESS - Selvia Noviyanti; Siska Sri Gustiani; Syifa Aulia Ramadani; Arsi Julaeha; Intan Rahma Sari (Jurnal Abdi Citra, 2026)
This Student Community Service (PMKM) activity aims to enhance the financial awareness of Micro, Small, and Medium Enterprise (MSME) actors through education on the separation of personal and business finances. Many MSME actors still mix personal money with business cash due to a lack of financial literacy, making it difficult to objectively assess business performance. In accounting principles, this practice violates the entity concept. The activity was carried out in an interactive counseling format based on three stages: experience-based presentation, direct demonstration and a reflective session. The material covers the definition of MSMEs, the importance of financial awareness, steps to separate finances, examples of simple bookkeeping, and the impacts and benefits of good financial management. The method used was an andragogy approach combined with demonstration, which are well-suited for adult learners. The results showed a significant increase in participants' understanding of the basic principles of business financial governance and the importance of separating personal accounts from business accounts.